1952
DOI: 10.1002/path.1700640115
|View full text |Cite
|
Sign up to set email alerts
|

Renal lesions in Leptospira canicola infection in dogs

Abstract: ACCORDING to serological surveys the incidence of Leptospira canicoh infection in dogs in different European countries has been computed t o vary between 3.6 per cent. in Rome and 44 per cent. in Belgium (Raven, 1941). A considerable proportion of dogs in this country is probably infected though most of the evidence is based on the somewhat selected dog population of veterinary clinics. Nevertheless, Stuart (1946), in Glasgow, found that 40 per cent. of 100 unselected domestic dogs gave serological proof of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

1956
1956
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(23 citation statements)
references
References 8 publications
0
23
0
Order By: Relevance
“…Naturally susceptible C3H/HeJ mice develop acute renal nephritis after experimental infection with Leptospira , but, to our knowledge, chronic carriage of Leptospira for several months in mice has not been described [24]. Despite a few previous studies mentioning renal fibrosis in dogs [2] and rats [23] infected with Leptospira , the putative mechanisms leading to renal fibrosis induced by chronic carriage of Leptospira have not been investigated. In the present study, we characterized a mild, but sustained, renal interstitial fibrosis occurring upon experimental infection of C57BL/6J mice with L. interrogans .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Naturally susceptible C3H/HeJ mice develop acute renal nephritis after experimental infection with Leptospira , but, to our knowledge, chronic carriage of Leptospira for several months in mice has not been described [24]. Despite a few previous studies mentioning renal fibrosis in dogs [2] and rats [23] infected with Leptospira , the putative mechanisms leading to renal fibrosis induced by chronic carriage of Leptospira have not been investigated. In the present study, we characterized a mild, but sustained, renal interstitial fibrosis occurring upon experimental infection of C57BL/6J mice with L. interrogans .…”
Section: Discussionmentioning
confidence: 95%
“…Fibrosis results in structural and functional renal alterations characterized by an excessive accumulation of extracellular matrix proteins in scarring tissues, which may lead to organ dysfunction [1]. From human and canine biopsy studies, leptospirosis has been shown to be associated with chronic interstitial nephritis and fibrosis [2]. Recently, it was reported that leptospirosis led to irreversible tubule-interstitial fibrosis in a young male, requiring continuous hemodialysis [3].…”
Section: Introductionmentioning
confidence: 99%
“…3,7,18,27,28 Lymphoplasmacytic lesions in dogs are strikingly similar to renal lesions of leptospirosis in humans. 27 These infiltrates are thought to function in local production of antileptospiral antibody and phagocytosis.…”
Section: Discussionmentioning
confidence: 72%
“…Leptospirosis was a significant cause of ATIN before the widespread use of antileptospiral bacterins. Mchtyre (19) and Timoney et a1 (38) estimated, by the use of antibody titers, that 20% to 40% of the dogs in the British Isles had been exposed to leptospires. This incidence has decreased dramatically with the use of vaccination.…”
Section: Diseases Of the Tubules And Interstitiuhfmentioning
confidence: 99%